Institutional Capacity Development of Rural Tourism In Lombok Kulon Bondowoso - Dedy Wijaya KUSUMA (Indonesia Strategic Sustainability, 2020)
The Indonesian government has tried to develop tourism based on the potential and ability of people to manage tourism activities. This strategy is realized through the development of a tourism village, one of which is the Lombok Kulon Tourism Village in Bondowoso Regency. This study aims to determine the institutional capacity in developing Lombok Kulon Tourism Village. The study was conducted with a descriptive qualitative method. The results of this study indicate that at the organizational level, the POKDARWIS